The inhibition effect of tannic acid on corrosion behaviour of HSLA steel in pure water - Qaban, Abdullah; Quazi, M. M.; Naher, Sumsun (World Research Library, 2019)
The effect of tannic acid on corrosion resistance of HSLA steel in pure water was studied by electrochemical technique using electrochemical impedance spectroscopy (EIS). The EIS data showed the beneficial effect of the addition of tannic acid in reducing the corrosion rate markedly, which indicates that the inhibitor molecules have the ability to reduce the severity of the corrosive attack. Increasing the inhibitor concentration from 1 to 5 g/l contributed further in increasing the corrosion resistance as indicated by the increase of the semicircle diameter in the Nyquist plots. This improvement was ascribed to the high absorbity of tannic acid molecules onto the steel surface so enriching the protectives layers that isolate the surface from the surrounding solution. The thickness and density of the layers are enhanced further as the inhibitor content increases, so giving less opportunity for the solution to penetrate into the steel and consequently preventing its dissolution.